Perancangan Aplikasi Website untuk Evaluasi Kinerja Karyawan di PT. Digital Aplikasi Solusi - KISNANDA, M FARHAN; Geni, Bias Yulisa (JATISI, 2024)
The rapid development of technology has prompted companies to enhance efficiency and effectiveness in employee performance evaluation. PT. Digital Aplikasi Solusi currently uses a manual method with Google Forms, leading to inconsistencies and difficulties in data analysis. This research aims to design a web application for employee performance evaluation using the Waterfall method, one of the models in the Software Development Life Cycle (SDLC). The application is built using PHP version 8 and the CodeIgniter 3 framework. Data collection methods included interviews, observations, and literature studies. The research stages encompass requirements analysis to application maintenance. The results of the conducted research indicate that the developed application is capable of improving efficiency and transparency in the employee performance evaluation process, facilitating the evaluation process, and providing accurate information for human resource management to support better decision-making in employee management.